2019
DOI: 10.1177/0954410019856836
|View full text |Cite
|
Sign up to set email alerts
|

Composite adaptive posicast controller for the wing rock phenomenon in a delta-wing aircraft

Abstract: The nonlinear dynamic phenomenon like wing rock is one of the important issues in the high performance aircraft autopilot design. This phenomenon occurs in the form of constant amplitude oscillations in the roll dynamics, during the flight at high angles of attack (AOAs) and endangers carrying out the mission of an aircraft. In this paper, a composite adaptive posicast controller is designed for the wing rock phenomenon in a delta-wing aircraft with known input delay. The existence of the input delay besides t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Several control strategies have been applied to alleviate the wing rock oscillations presented as follows. A composite adaptive posicast controller for the wing rock control in the presence of known input delay is proposed by Yousefimanesh et al 42 The proposed method consists of composite adaptive posicast control and linear quadratic regulator (LQR) controllers. It has been shown that the LQR+MRAC controller has good tracking performance against input delay and uncertainties while LQR is not able to resist against them.…”
Section: Introductionmentioning
confidence: 99%
“…Several control strategies have been applied to alleviate the wing rock oscillations presented as follows. A composite adaptive posicast controller for the wing rock control in the presence of known input delay is proposed by Yousefimanesh et al 42 The proposed method consists of composite adaptive posicast control and linear quadratic regulator (LQR) controllers. It has been shown that the LQR+MRAC controller has good tracking performance against input delay and uncertainties while LQR is not able to resist against them.…”
Section: Introductionmentioning
confidence: 99%